The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/pssb.201147445
|View full text |Cite
|
Sign up to set email alerts
|

Electronic states and nonlinear optical properties of a two‐dimensional hexagonal quantum dot: Effects of impurity, geometrical size and confinement potential

Abstract: Phone: þ98 741 222 3048, Fax: þ98 741 222 3048In the present work, the linear and the third-order nonlinear optical absorption coefficients as well as refractive-index changes in a two-dimensional hexagonal quantum dot with the presence of an impurity are calculated. A matrix diagonalization method is used to calculate energy levels and corresponding wave functions in the effective-mass approximation. Also, by means of the compact-density matrix approach the linear and nonlinear optical absorption coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Thus, the impurity driven modulation of linear and nonlinear optical properties has persistently gained importance because of emerging applications in photodetectors and high‐speed electro‐optical devices (). Naturally, a good number of theoretical and experimental works have been conducted on both linear and nonlinear optical properties of these structures .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the impurity driven modulation of linear and nonlinear optical properties has persistently gained importance because of emerging applications in photodetectors and high‐speed electro‐optical devices (). Naturally, a good number of theoretical and experimental works have been conducted on both linear and nonlinear optical properties of these structures .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, with the advances in nanofabrication technologies like R. Khordad & H. Bahramiyan epitaxial techniques and metal-organic chemical vapor deposition, [6][7][8] it is possible for researchers to fabricate quantum wire structures of nanometer size with various cross-sections such as triangular, parallelogram, V-shape, T-shape, square, circular and hexagonal. [9][10][11][12] For example, Tsetseri et al 13 calculated the low-temperature electron mobility in V-shaped quantum well wires. Mohan et al 14 investigated the spectrum of luminescent hexagon superlattice, created by InP/InAs/InP nanotubes with the transversal cross-section of right hexagon shape.…”
Section: Introductionmentioning
confidence: 99%
“…S M Azami et al studied the energy levels, the nonlinear OACs, and refractive index changes in a two-dimensional hexagonal QD [13]. G. Rezaei et al calculated the influence of a center hydrogenic impurity on the nonlinear refractive index changes and OACs in a two-dimensional hexagonal QD [14]. The numerical results above showed that the size of the QD, confined potential, hydrogenic impurity, and external fields play an essential role in the nonlinear optical properties.…”
Section: Introductionmentioning
confidence: 99%